Comportamento do camarão de água doce macrobrachium rosenbergii (De Man, 1879) em cultivos misto e monossexo - Santos, Daniele Bezerra dos (2013)
Understanding the behavioral activities of freshwater shrimp in captivity is of paramount importance for the appropriate management of the species. In Brazil, the shrimp Macrobrachium rosenbergii is currently the most widely used species in the freshwater shrimp culture due to its high potential for cultivation and good market acceptance. Thus, the present study aimed to describe and characterize the behavioral activities of M. rosenbergii in monosex and in mixed (male and female) (manuscript 1, 2 and 3) populations and the growth performance of this species in restrictive feeding conditions and in different feeding management (manuscript 4 and 5, respectively) . Juvenile and adult shrimps were collected from ponds of the Aquaculture Station - Unidade Especializada em Ciências Agrárias - Universidade Federal do Rio Grande do Norte (UFRN), Macaíba/RN and then transferred to the Laboratório de Estudos do Comportamento do Camarão LECC (Laboratory for Shrimp Behavioral Studies) of the Universidade Federal do Rio Grande do Norte (UFRN). For each treatment , eight aquaria of 250 L (50 cm x 50 cm x 100 cm) were used in a closed recirculating water system with artificial lighting, constant aeration , continuous filtration through a biochemical and biological filter (canister filter), and fine sand as substrate . The water quality was monitored daily. The lab consisted of two rooms with artificial lighting system , controlled by a timer with dark / light cycle of 12:12 h . In manuscript 1, the behavioral categories of the species were presented through an ethogram, which described 31 behaviors, subdivided into general and agonistic behaviors. Manuscript 2 compared the behavioral profile of shrimps in male and in female monosex and mixed populations over 24 hours in laboratory. In three types (mixed, male monosex and female monosex) of populations during the light and dark phases of the 24 hour cycle, the shrimps showed higher occurrence of cleaning behavior. Manuscript 3 examined the influence of the color of the shelter on the frequency of its use and behavioral activities of shrimp in mixed, in male monosex and in female monosex populations over 24 hours. We observed that the shrimp M. rosenbergii burrow more frequently during the light phase in male monosex and mixed populations; they also tend to choose the black shelters. Female monosex populations tend to use red and orange shelters. In manuscript 4, we evaluated in laboratory the behavioral activities and growth performance of juvenile shrimps under food restriction. We observed that a mild food restriction may be used since there is no loss concerning the growth of the animals; feeding management on alternate days , compared to daily management can be financially productive both reducing labor costs and reducing the amount of feed used . Manuscript 5 evaluated the behavior of shrimps in monosex and in mixed populations, as well as the latency of reach the food according to feed offer (tray or food dispersal) . Our results indicate that animals adjust to both types of feed offer food dispersal as much as tray, but they spend more time to reach the feed when it is offered in trays (feeders). Comparing culture types (mixed, male monosex and female monosex), the latency to reach the food was lower for female monosex population. The data obtained in this study demonstrate the importance of identifying different pressures and environmental stimuli on the behavioral responses of this species. This knowledge would support management improvement to optimize the levels of animals‟ welfare, resulting in a better zootecnical performance